Associations of the triglyceride-glucose index and its combined indices with non-suicidal self-injury in adolescents with depressive disorders: the mediating role of sleep quality - Liu, Pu-Le; Gao, Shou; Zhang, Yan; Li, Jiao; Du, Jing; Yang, Ning; Dong, Qiang-Li (Frontiers in Psychiatry, 2025)
ObjectiveThis study examined the associations between the Triglyceride-Glucose (TyG) index and its combined indices (TyG-BMI, TyG-WC, TyG-WHtR) with non-suicidal self-injury (NSSI) in adolescents with Major Depressive Disorder (MDD). It also explored whether sleep quality mediated these relationships.MethodA total of 157 adolescents (12–18 years) with MDD were recruited. Participants were divided into NSSI (n = 78) and non-NSSI (n = 79) groups based on DSM-5 criteria. The TyG index and its derivatives were calculated from fasting blood samples. Analyses included multivariable logistic regression, restricted cubic spline (RCS) analysis, mediation analysis, and receiver operating characteristic (ROC) curves.ResultsThe NSSI group had higher TyG index values (Median [Q1, Q3]: 8.23 [7.95, 8.45]) than the non-NSSI group (7.73 [7.33, 8.21], P < 0.001). Adjusted regression models confirmed significant associations between TyG indices and NSSI (e.g., TyG: OR = 3.50, 95% CI: 1.82–6.74, P < 0.001), especially in female adolescents. Sleep quality partially mediated the link between TyG and NSSI (proportion mediated = 17.1%, P = 0.026). ROC analysis showed moderate predictive accuracy for TyG-WC (AUC = 0.745, 95% CI: 0.666–0.824).ConclusionThe TyG index and its combined indices are positively associated with NSSI in adolescents with MDD. Sleep quality partially mediates this relationship. These indices may serve as low-cost markers for early identification of adolescents at risk for NSSI in clinical practice.